2020
DOI: 10.1186/s12889-020-08952-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of Treponema pallidum infection in a rural area of southwestern China

Abstract: Background: Epidemiological data on Treponema pallidum infection are scarce from the southwestern region of China. The purpose of this study was to determine the distribution and determinants of T. pallidum infection in the region. Methods: A community-based cross-sectional study of 2608 participants aged ≥14 years was conducted in a rural area of southwestern China in 2014-15. A pretested questionnaire was used to collect sociodemographic characteristics and other factors associated with T. pallidum infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
4
1
2
Order By: Relevance
“…In China, Li and Yi ethnic minorities appear to have a higher prevalence of HCV (7.0% exposed and 2.7% with active infection respectively) compared to the general population (0.7% exposed). Tattooing has been hypothesized as a potential route of transmission among Li people [ 19 ], while injection drug use is a probable route of transmission among the Yi ethnic minority [ 20 ]. Five studies reported HCV prevalence among migrants (Australia, the Republic of Korea, and three in China).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, Li and Yi ethnic minorities appear to have a higher prevalence of HCV (7.0% exposed and 2.7% with active infection respectively) compared to the general population (0.7% exposed). Tattooing has been hypothesized as a potential route of transmission among Li people [ 19 ], while injection drug use is a probable route of transmission among the Yi ethnic minority [ 20 ]. Five studies reported HCV prevalence among migrants (Australia, the Republic of Korea, and three in China).…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [ 10 , 11 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Table A1unclassified
See 2 more Smart Citations
“…Adicionalmente, estudios de otros países en población general han reportado prevalencias más bajas. Así, en Guinea Bissau, en 500 personas con edades entre 16 y 49 años, fue del 0,8 % [20]; en 210 mujeres de una universidad de Brasil, del 1,9 % [21], y en 2608 sujetos de una zona rural del suroeste China, fue del 1,2 % [22].…”
Section: Discussionunclassified